Pembuatan Sudut Literasi Pada Pengembangan Potensi Anak Usia Dini (PAUD) Dan Edukasi Kebersihan Lingkungan Sekitar - Muhammad Fikry Ardiansyah; Ackmal Rafli; Sarah Wulanfiani; Laraswati Ramadhani; Syarif Maulana (Jurnal Pengabdian Kepada Masyarakat, 2023)
Our Community Service Program is about "Creating a Literacy Corner for Developing Potential Early Childhood (PAUD) and Education on Environmental Hygiene and How to Wash Hands Correctly." they do not constantly look at gadgets or cellphones and it is hoped that reading interest in Indonesia can increase again because our reading interest is in the 60th place out of 61 countries about reading interest, which means only 0.0001% or only 1 person who is interested to read therefore the literacy corner program itself can be a breakthrough for young people so that interest in reading does not disappear but instead develops in the future, Then as for our second program where we focus on the cleanliness of the surrounding environment through; Not littering, Cleanliness in terms of dressing, And how to wash hands properly and correctly. Because there are still many people who are not aware or still take it lightly about cleanliness in the surrounding environment, therefore we care about it as well as a form of prevention from disease outbreaks that continue to haunt us all this time.